Evaluation of the Performance of Tabriz Islamic City Council (case study of Tabriz Munıcıpalıty’s constructional projects) - Yaguoob Alavi Matın; Alireza Dadjouyan; Farhad Nejhad Irani (مدیریت بهره وری, 2009)
Accordıng to Act 7 of the constitution, the Islamic cıty councils must continuously supervise the performance of munıcipalitıes such as their programs and projects; therefore this dissertation tries to evaluate the constructional projects of TabrizMunicipality divided into three categories: roads, buildings and civil facilities. The evalution involves three dimensions: supervision before implementation, supervision during implementation and supervision after implementation. The survey population is the eight areas of the Municipality. The sample number is 31, the measurment instrument is a questionnaire, and the research is a correlational one. After analysing the data, the scale of the council supervision is shown and some suggestions are given to elevate the supervision state.